Integrasi Nilai-Nilai Pendidikan Karakter Melalui Aktivitas Sepak Bola di SD Negeri 1 : Integrasi Nilai-Nilai Pendidikan Karakter Melalui Aktivitas Sepak Bola di SD Negeri 1 - Muhammad Fajril Rifaldo; leksono, Kuat; Vito Indarto, Asyidika; Wahyudi, Apri (Universitas Negeri Medan, 2025)
Character education is a crucial component in shaping students' personalities from an early age. One effective approach to instilling character values is through sports activities, particularly football. This study aims to describe the integration of character education values through football activities at SD Negeri 1 Surabaya Kedaton. A qualitative descriptive approach was used, involving physical education teachers, football extracurricular coaches, and student participants as research subjects. Data were collected through observation, in-depth interviews, and documentation. The data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing/verification. The results of the study show that football activities serve as a strategic medium to instill values such as discipline, teamwork, sportsmanship, leadership, responsibility, patience, and self-control. Students are consistently trained to be punctual, respect opponents, communicate within the team, and comply with established rules. Furthermore, the roles of teachers and coaches are crucial in guiding students to apply these character values in their daily lives, both on and off the field. This study concludes that football can be an effective and contextual medium for character education in primary school environments. The findings are expected to serve as a reference for curriculum developers and education practitioners in designing extracurricular programs that promote sustainable character development. Keywords: character education, football, primary school, extracurricular, moral values.